Characteristics and predictors of low-grade renal artery stenosis in female patients with CKD. (31st December 2023) - Wu, Deping; Nie, Jinli; Lin, Huagang; Zhang, Dexian; Ye, Zhibin; Zhang, Wan; Xiao, Jing
ABSTRACT: Aim: Renal artery stenosis (RAS) is an important cause of chronic kidney disease (CKD). The main purpose of this study was to explore the clinical characteristics and predictors of low-grade RAS in female patients with CKD. Methods: One hundred and five female CKD patients from Huadong Hospital affiliated with Fudan University who underwent 3 T non-contrast renal artery magnetic resonance angiography (MRA) were analyzed. Basic statistics methods were used in the study, such as independent-sample t test, non-parametric test, binary logistic regression analysis and ROC analysis. Results: In this cross-sectional study, there were 50 patients with RAS and 55 without RAS (47.6% versus 52.4%). Binary logistic regression analysis demonstrated that low-level ALB and lymphocyte count, high-level SP, BUN and NLR were independent risk factors for low-grade RAS in female patients with CKD. ROC analysis indicated that eGFR, FeNa and UBCR, ALB, lymphocyte count and NLR had the best predictive value for low-grade RAS, especially eGFR with a sensitivity of 65.50% and specificity of 72.00% and FeNa with a sensitivity of 71.10% and specificity of 72.20% and BUCR with a sensitivity of 71.10% and specificity of 68.10%. Conclusion: In female patients with CKD, FeNa, eGFR, ALB, UBCR, lymphocyte count and NLR may be good predictors of low-grade RAS, especially eGFR, FeNa and BUCR. Graphical abstract: uf0001